Comparative analysis of enzymatic activity of tannase in non-conventional yeasts to produce ellagic acid - Márquez-López,Anahí (2020)
Abstract Non-conventional yeasts represent an alternative for microorganisms that are capable to produce the enzyme Tannase (EC 3.1.1.20), which has many applications is the food and pharmaceutical industry as it stands out for its ability to produce ellagic acid out of the enzymatic hydrolysis of ellagitannins. Ellagic acid has been studied in the medical area for its action against various diseases, as is the case of cancer or heart problems. The investigation was conducted to evaluate seven non-conventional yeasts - Debaryomyces hansenii PYC ISA 1510, Debaryomyces hansenii PYC 2968, Candida parapsilosis, Candida utilis, Pichia pastoris, Pichia kluyveri, Issatchenkia terricola - as producers of the enzyme tannase. This was done in mediums of fermentation with tannic acid (1-3%) and YPD without tannic acid, to determine the activity of the enzyme by two spectrophotometric methods, the first being with rhodamine and the second with methyl gallate, to detect the presence of gallic acid as a product of the hydrolysis of tannic acid. The main results showed that the evaluated non-conventional yeasts all presented activity with the Tannase enzyme, obtaining better detection results with the rhodamine technique for the stability of the formed complex, which gives more precision of the obtained data.